1983
DOI: 10.1073/pnas.80.9.2651
|View full text |Cite
|
Sign up to set email alerts
|

Transferrin as a fetal growth factor: acquisition of responsiveness related to embryonic induction.

Abstract: Differentiation of the metanephric mesenchyme, which is triggered by an inductive tissue interaction, has been shown to proceed in a chemically defined medium containing transferrin. Here, we report that neither transferrin-depleted serum nor a chemically defined medium devoid of transferrin promote differentiation and that activity can be restored by the addition of transferrin. It thus appears that we have identified the serum factor required for kidney differentiation. Transferrin seems to affect differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
0
1

Year Published

1988
1988
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(63 citation statements)
references
References 44 publications
3
59
0
1
Order By: Relevance
“…It is interesting that TfR is expressed on the apical membrane of proximal tubule and collecting duct cells in mice (Figure 1), in distal convoluted tubules in the medulla of rats (20), and in all tubules in humans (21), offering a straightforward mechanism by which Tf can be retrieved from filtrate ( Figure 2). It has been found that Tf is an essential growth factor in the development of kidney and differentiation of tubule (22), and retrieval of Tf from filtrate may be the major mechanism by which proximal tubule cells acquire the iron that they need (19).…”
Section: Renal Filtration Of Tf and Proximal Tubule Resorptionmentioning
confidence: 99%
“…It is interesting that TfR is expressed on the apical membrane of proximal tubule and collecting duct cells in mice (Figure 1), in distal convoluted tubules in the medulla of rats (20), and in all tubules in humans (21), offering a straightforward mechanism by which Tf can be retrieved from filtrate ( Figure 2). It has been found that Tf is an essential growth factor in the development of kidney and differentiation of tubule (22), and retrieval of Tf from filtrate may be the major mechanism by which proximal tubule cells acquire the iron that they need (19).…”
Section: Renal Filtration Of Tf and Proximal Tubule Resorptionmentioning
confidence: 99%
“…A similar situation may occur in brain where the transferrin produced by oligodendrocytes and other cells probably plays atrophic role on developing neurons and astrocytes (Aizenman et al, 1986). Finally a role for transferrin and its receptor in embryonic morphogenesis has been shown by Ekblom et al (1983) in mouse organ cultures of developing kidneys and teeth (Partanen et al, 1984). Transferrin is necessary to cell proliferation and cell differentiation.…”
Section: Discussionmentioning
confidence: 97%
“…It is widely accepted that the major role of transferrin is iron transport and delivery to cells and tissues, nevertheless it has also been proposed that transferrin is important for growth and differentiation of several cell types. In particular, transferrin seems to play a significant role as a mitogenic factor (Trowbridge and Omary, 1981), as a neuro- (Aizenman et al, 1986) and myotrophic agent (Li et al, 1982) and in embryonic morphogenesis (Ekblom et al, 1983;Partanen et al, 1984).…”
mentioning
confidence: 99%
“…Metanephric kidneys were dissected from LacZ positive embryos and grown for 6 days in the presence or absence of 7nM MK, at 37˚C, 5% CO 2 on 0.4 µm pore size transwells as described above. Kidneys were fixed in 4% paraformaldehyde for 1.5 hours and washed with tissue rinse solution A (0.1 M PO 4 6 ) for 1 hour at 37˚C. The tissues were then processed for paraffin sectioning using Histogel.…”
Section: A B C Dmentioning
confidence: 99%
“…[1][2][3] The identification of the epithelial-mesenchymal signaling pathways responsible for these complex inductive events has been a major objective in the effort to understand kidney organogenesis in molecular terms. The ureteric bud provides essential survival factors for the metanephric mesenchyme [4][5][6] and recent studies employing metanephric organ culture have demonstrated that Tissue Inhibitor of Metalloproteinase II (TIMP2), 7 Fibroblast Growth Factor 2 (FGF2) and Bone Morphogenetic Protein 7 ( BMP7) may play important roles in these processes. 8,9 In turn, retinoid-dependent mesenchymal stromal cell signaling activates ureteric bud branching morphogenesis by maintaining the expression of the c-ret receptor tyrosine kinase in the ureteric bud epithelium 10 which functions as the signal transducer for the mesenchymal cell-secreted factor GDNF.…”
Section: Introductionmentioning
confidence: 99%